Postoperative pain treatment with continuous epidural analgesia after spinal fusion surgery - Wnęk, Włodzimierz; Zajączkowska, Renata; Sienkiel, Walery; Snela, Sławomir (European Journal of Clinical and Experimental Medicine, 2005)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Patients undergoing spinal surgery may experience significant postoperative pain. Spinal fusion is a major procedure which often causes problems with postoperative analgesia. One possible solution involves the placement of epidural catheters under direct vision by the surgeon at the end of the procedure, followed by an epidural infusion of local anaesthetic. Epidural analgesia has previously been shown to be safe and effective and may offer some advantages over opioid-based postoperative analgesia. We report an observational study of the analgesia achieved with the use of surgically placed epidural catheters. Twenty patients who underwent spinal fusion surgery had epidural catheters placed by the surgeon intraoperatively. A bolus of bupivacaine 0,25% was given postoperatively, followed by an infusion of bupivacaine 0,125% with fentanyl 2 μg/ml. The technique provided efficient postoperative analgesia without major postoperative complications.